2017
DOI: 10.3389/fpls.2017.01833
|View full text |Cite
|
Sign up to set email alerts
|

Cosmopolitan Species As Models for Ecophysiological Responses to Global Change: The Common Reed Phragmites australis

Abstract: Phragmites australis is a cosmopolitan grass and often the dominant species in the ecosystems it inhabits. Due to high intraspecific diversity and phenotypic plasticity, P. australis has an extensive ecological amplitude and a great capacity to acclimate to adverse environmental conditions; it can therefore offer valuable insights into plant responses to global change. Here we review the ecology and ecophysiology of prominent P. australis lineages and their responses to multiple forms of global change. Key fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
101
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 127 publications
(101 citation statements)
references
References 263 publications
0
101
0
Order By: Relevance
“…Previous studies have found that P. australis demonstrates lineage‐specific responses to increases in temperature that include morphology, growth, and some traits related to photosynthesis (reviewed in Packer et al 2016, Eller et al 2017). Others have noted plasticity in some P. australis traits both in its native and introduce ranges, but particularly for the invasive lineage in North America (Mozdzer et al 2013, Douhovnikoff et al 2016, Bhattarai et al 2017, Eller et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found that P. australis demonstrates lineage‐specific responses to increases in temperature that include morphology, growth, and some traits related to photosynthesis (reviewed in Packer et al 2016, Eller et al 2017). Others have noted plasticity in some P. australis traits both in its native and introduce ranges, but particularly for the invasive lineage in North America (Mozdzer et al 2013, Douhovnikoff et al 2016, Bhattarai et al 2017, Eller et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…§ § 703-712). High-intensity summer livestock grazing also has the potential to reduce Phragmites inflorescence production Duncan et al, 2019;Silliman et al, 2014) and could be used in replacement of mowing in some management sequences. We observed Phragmites inflorescence production increase once treatments ceased, as Phragmites began to reinvade, further emphasizing the importance of continuing follow-up treatments beyond a 3-year cycle.…”
Section: Treatments Differentially Influence Phragmites Inflorescenmentioning
confidence: 99%
“…Meanwhile, the strong signal of human activities on P. australis distribution and dispersal can mediate these two patterns via IBH. Phragmites australis thus provides an ideal model to study the evolutionary mechanisms involved in plant invasions (Eller et al, 2017;Meyerson, Cronin, & Pyšek, 2016).…”
Section: Introductionmentioning
confidence: 99%